Growth and Productivity of Ginger (Zingiber offieinale Rosc.) under Kapok (Ceiba pentandra (L.) Gaertn based Agri-silviculture System - Prajapati, R. K.; Nongrum, Kitboklang; Singh, Lalji (Indian Journal of Agroforestry, 2020)
Field experiment was conducted to evaluate the growth and productivity of ginger under Ceiba pentandra (L.) Gaertn. based agri-silvicultural system. The system comprises three crown pruning management of Ceiba pentandra (L.) Gaertn. (upto 25%, unpruned crown and without trees control) and four treatments of farmyard manure (FYM) (0 Mg ha-1, 10 Mg ha-1, 20 Mg ha-1 and 30 Mg ha-1). The experiment was laid out in a split plot design with three replications following crown pruning management as main plots and FYM as sub-plots. The result shows that the growth and biomass of ginger were higher in un-pruned Ceiba pentandra (L.) Gaertn. An increase with the increased dose of FYM was prominent. Rhizome yield varied from 9.89 Mg ha-1 to 14.39 Mg ha-1 under different crown pruning management and responded positively to the increasing dose of FYM. RH was higher under the tree canopies with un-pruned as the highest. The temperature at the leaf surface of ginger Increased with the increase in crown density. PAR was also reduced due to higher crown density with the least in without trees control. Soil nutrients were reduced after the harvests of the ginger crops with a slight increased in soil organic C and pH. From economic consideration, un-pruned Ceiba pentandra and FYM @ 30 Mg ha-1 resulted in higher net realization per hectare, and return per rupee invested, both individually as well as in combination